2022
DOI: 10.1038/s41467-022-34105-y
|View full text |Cite
|
Sign up to set email alerts
|

Multiple sources of aerobic methane production in aquatic ecosystems include bacterial photosynthesis

Abstract: Aquatic ecosystems are globally significant sources of the greenhouse gas methane to the atmosphere. Until recently, methane production was thought to be a strictly anaerobic process confined primarily to anoxic sediments. However, supersaturation of methane in oxygenated waters has been consistently observed in lakes and the ocean (termed the ‘methane paradox’), indicating that methane can be produced under oxic conditions through unclear mechanisms. Here we show aerobic methane production from multiple sourc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 84 publications
(129 reference statements)
3
21
1
Order By: Relevance
“…CH 4 decreased during the dark period of their experiment due to off‐gassing, which no doubt occurs in open environments such as the YR. However, the minimum CH 4 concentrations during maximum solar irradiance observed in the current study are difficult to reconcile with that pure culture work (Bižić et al 2020) or lake water incubations (Perez‐Coronel and Michael Beman 2022), where CH 4 synthesis positively correlated with photosynthesis and increasing light level [17].…”
Section: Discussioncontrasting
confidence: 68%
“…CH 4 decreased during the dark period of their experiment due to off‐gassing, which no doubt occurs in open environments such as the YR. However, the minimum CH 4 concentrations during maximum solar irradiance observed in the current study are difficult to reconcile with that pure culture work (Bižić et al 2020) or lake water incubations (Perez‐Coronel and Michael Beman 2022), where CH 4 synthesis positively correlated with photosynthesis and increasing light level [17].…”
Section: Discussioncontrasting
confidence: 68%
“…Based on the stable carbon isotope mass balance of CH 4 produced and the correlation between CH 4 and chlorophyll, these research teams suggested phytoplanktonic CH 4 production as a likely source to explain the CH 4 oversaturation in the epilimnion during spring and summer. This hypothesis has recently been strongly supported by Perez‐Coronel and Beman (2022) that associated aerobic CH 4 production with (bacterio)chlorophyll metabolism and photosynthesis. δ 13 C‐CH 4_source values of oxic CH 4 production in surface water were distinct from the much more negative δ 13 C‐CH 4 values measured in sediment pore water produced by methanogenic archaea (Hartmann et al., 2020; Thottathil et al., 2022).…”
Section: Resultsmentioning
confidence: 63%
“…CH 4 concentrations increased four‐fold across time in all tanks and were higher in the burned treatment at the end of the experiment. Natural ponds and lakes account for 67% of CH 4 emissions from inland waters (Pilla et al., 2022), and the progressive rise in methane across our experiment may be the result of an increase in anaerobic methanogenesis localized within the detritus mesh bags as well as aerobic methanogenesis produced during bacterial photosynthesis (Perez‐Coronel & Beman, 2022). The trend for higher CH 4 in the burned‐detritus mesocosms at the end of the experiment, may likewise relate to greater autochthony and NPP in burned tanks also acting to stimulate bacterial methanogenesis.…”
Section: Discussionmentioning
confidence: 87%